The Business of community newspapers status, problems and prospects of community newspapers in Quezon Province - Morong, Joseph Thaddeus E.
This is a study of eight community newspapers in Quezon Province. It tried to find out how they articulate the concerns of the local community, serving as both information provider and venue for public debate. The community newspapers in this study claim that their newspapers are out to serve the interest of the general public, that they see themselves as serving some social, political, or cultural cause. Are they fulfilling the caus? Apparently they are not. Many of them operate as family business enterprises with profit as the topmost priority. No wonder they do not have yet the organization that could handle the professional operations. This study also reveals the profile of community newspapers in Quezon Province since similar studies were conducted.